2023
DOI: 10.1111/een.13269
|View full text |Cite
|
Sign up to set email alerts
|

Social but not solitary bee abundance tracks pollen protein accumulation in forest canopy gaps

Abstract: Forest restoration projects that create canopy gaps can promote floral diversity and may provide reservoirs for bee–flower interactions. However, periods of bee activity must match availability of floral nutrition for bees to benefit from these effects. We model variation in canopy gap size, floral density, pollen protein and bee and floral traits to test the hypothesis that patterns of floral visitation in bee–flower interactions are predicted by patch structure, variation in bee life histories and floral phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Thus, weed-removal efforts could affect bee foraging activity, as eradication effort s would substantially reduce floral resources available to bees in some areas. Some thistles (e.g., Carduus nutans , also an invasive species in Colorado) have highly nutritious pollen ( Davies and Davis 2023 ) and inflorescences are available throughout much of the growing season. However, studies focusing on Cirsium arvense specifically have demonstrated that the presence of C. arvense attracts floral visitors away from native forbs ( Daniels and Arceo-Gómez 2020 ).…”
Section: Responsementioning
confidence: 99%
“…Thus, weed-removal efforts could affect bee foraging activity, as eradication effort s would substantially reduce floral resources available to bees in some areas. Some thistles (e.g., Carduus nutans , also an invasive species in Colorado) have highly nutritious pollen ( Davies and Davis 2023 ) and inflorescences are available throughout much of the growing season. However, studies focusing on Cirsium arvense specifically have demonstrated that the presence of C. arvense attracts floral visitors away from native forbs ( Daniels and Arceo-Gómez 2020 ).…”
Section: Responsementioning
confidence: 99%